2011
DOI: 10.1016/j.pbb.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

An acetaldehyde-sequestering agent inhibits appetitive reinforcement and behavioral stimulation induced by ethanol in preweanling rats

Abstract: Ethanol's motivational consequences have been related to the actions of acetaldehyde, a metabolic product of ethanol oxidation. The present study assessed the role of acetaldehyde in the motivational effects of ethanol on pre-weanling rats. In Experiment 1 pups (postnatal days 13-14, PD 13-14) were given systemic administration of d-penicillamine (DP, a drug that sequesters acetaldehyde: 0, 25, 50 or 75 mg/kg) before pairings of 1.0 g/kg ethanol and a rough surface (sandpaper, conditioned stimulus, CS). At tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…For this reason, it has been proposed that brain-EtOH-derived acetaldehyde could play a role in some of the psychopharmacological effects caused by EtOH. In agreement to this, it has been observed that administration of acetaldehyde chelating agents, such as D-penicillamine and L-cysteine, prevents a wide range of EtOH-elicited behaviors, including EtOH intake (Font et al, 2005(Font et al, , 2006Mart ı-Prats et al, 2010;Pautassi et al, 2010;Peana et al, 2010). The results obtained in this study indicated that H 2 O 2 levels are critical to EtOH intake.…”
Section: Discussionsupporting
confidence: 87%
“…For this reason, it has been proposed that brain-EtOH-derived acetaldehyde could play a role in some of the psychopharmacological effects caused by EtOH. In agreement to this, it has been observed that administration of acetaldehyde chelating agents, such as D-penicillamine and L-cysteine, prevents a wide range of EtOH-elicited behaviors, including EtOH intake (Font et al, 2005(Font et al, , 2006Mart ı-Prats et al, 2010;Pautassi et al, 2010;Peana et al, 2010). The results obtained in this study indicated that H 2 O 2 levels are critical to EtOH intake.…”
Section: Discussionsupporting
confidence: 87%
“…Many laboratories have tested the role of the ethanol metabolite acetaldehyde, by impairing its formation (see Correa et al, 2011 for review) or using acetaldehyde sequestering agents such as D-penicilamine (Enrico et al, 2009;Martí-Prats et al, 2010;Pautassi et al, 2010). All of these in vivo studies have shown that the behavioral, neurochemical, and electrophysiological properties of ethanol are impaired when acetaldehyde, and conse- quently salsolinol, cannot be formed (Enrico et al, 2009;Martí-Prats et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, administration of either D-penicillamine or L-cysteine effectively reduced EtOH consumption and decreased EtOH conditioned place preference (CPP) in rats (Font et al, 2006b; Diana et al, 2008; Peana et al, 2008). Intra-cisterna magna injections of D-pennicillamine acted to block EtOH- and/or ACD appetitive conditioning to a surrogate nipple in newborn rats (March et al, 2013) and induced locomotor activity and tactile stimulus preference in preweanling rats (Pautassi et al, 2011). Mice exhibit a decrease in EtOH CPP and a reduction in EtOH-induced motor depression when treated with D-penicillamine (Font et al, 2005, 2006a).…”
Section: Implication Of Acd In the Central Actions Of Etohmentioning
confidence: 99%
“…Adult rats peripherally treated with ACD exhibit a dose-dependent preference to a discrete olfactory stimulus (Quertemont and DeWitte, 2001). Rat pups exhibited a significant preference to an olfactory cue previously paired with ACD exposure (March et al, 2013) while pre-weanling rats exhibited an ACD-dependent stimulation of locomotor activity and tactile stimulus preference following EtOH administration (Nizhnikov et al, 2007; Pautassi et al, 2011). ACD has been shown to dose-dependently alter locomotor activity in adult animals as well.…”
Section: Acd Exhibits Rewarding Propertiesmentioning
confidence: 99%